Handbook on austerity, populism and the welfare state - Greve, Bent, 1953- (Edward Elgar Publishing, 2021)
"This innovative Handbook presents the core concepts associated with austerity, retrenchment and populism and explores how they can be used to analyse developments in different welfare states and in specific social policies. Leading experts highlight how these concepts have influenced and changed welfare states around the globe and impacted specific areas including pensions, long-term care, the labour market, taxation, social activism and gender equality. Comprehensive in approach, the authors offer cutting edge research demonstrating the importance of societal developments to welfare states and the effects of ideas, ideologies and variations in policies and decisions in different countries. They also investigate key country and regime-specific approaches to welfare state development, analysing and interpreting changes in the last 10-15 years. The main drivers for these changes, ranging from demography, to the financial crisis, to the use of new technology and the possible impact of populism, are examined. Far reaching and authoritative, this timely Handbook offers a systematic theoretic overview which will be invaluable for scholars of welfare states, social policy, sociology and political science. Social policy makers will also benefit from the novel case studies explored in depth, and suggestions for potential policy changes"--